Introduction: The Social Responsibility of Lawyers - Karen Tokarz (Washington University Journal of Law & Policy, 2004)
This volume marks the fifth annual volume published by the Washington University Journal of Law & Policy dedicated to Access to Justice. Each year, the special issue includes articles from nationally and internationally prominent academics and practitioners—from diverse backgrounds in areas such as international human rights, the economics of poverty, racial justice, capital punishment, clinical legal education, government public service, and pro bono private practice—who share a commitment to access to justice. Many of the articles are drawn from presentations in the School of Law’s annual Public Interest Law Speakers Series, entitled Access to Justice: The Social Responsibility of Lawyers. This Series introduces our community to the ideas of outstanding academics and practitioners, highlights the responsibility of lawyers to ensure access to justice, and provides a forum for the law school and the wider University community to engage in a discussion of legal, social, and ethical issues that bear upon access to justice. This Series, begun in 1998–99, was developed in celebration of the twenty-fifth anniversary of the School’s nationally recognized Clinical Education Program, through which many of our students are introduced to public service and public interest law practice. Some of the articles are drawn from the Clinical Education Program’s annual Access to Equal Justice Colloquium on Creating Collaborations Between the University and the Community to Improve Access to Justice in Our Region. This colloquium, initiated in 2000–01 by the Association of American Law Schools, brings together civil and criminal attorneys; community leaders; government officials; judges; and faculty, staff, and students from local law schools and universities to collaborate on improving access to justice and the delivery of legal services in the region. This volume, like the prior four volumes, provides a truly inspirational look, through the words and stories of real leaders, at the broad social justice responsibilities and aspirations of lawyers to foster access to justice for all.
Keywords: Access to justice; Equality; Social responsibility; Legal profession